A preliminary study of ulcerative disease in koi carps (Cyprinus carpio, Linnaeus) - Mohd Daud, Hassan; Butprom, Sureerat; Mohamed Mustapha, Noordin; Zakaria, Zunita (Universiti Putra Malaysia Press, 2004)
A chronic persistent ulcerative disease was reported in coloured carps or Koi carps (Cyprinus carpio) in several commercial aquarium fish holding facilities and retailer shops. A preliminary histopathological study was carried out to elucidate the pathological signs seen. The ulcer was characterized by tissues edema and necrosis with chronic inflammatory response. Findings showed that in severe ulcer development it also involved deep muscle layers and sometimes exposing the bone. In most of the affected fish the abdomen were slightly swollen and filled with a clear yellow or red-tinged ascetic fluid. Liver and kidney were pale in colour, swollen and friable. In cut sections, mild to severe cellular changes such as diffuse haemorrhage, cell necrosis and degeneration were seen in the skin, muscles, gills, kidney, liver, spleen and intestines. Electron microscopy ofthe infected tissues showed the presence of two virus particles, morphologically similar to Coronavirus and Reovirus.